The Romans - Forman, Joan, 1919-; Weston, Verity; Connolly, Peter; Thornley, Peter (London : Macdonald Educational Morristown, N.J. : Silver Burdett Co., 1975)
Introduces the civilization of ancient Rome.
Includes index.
Keywords: Rome -- Civilization -- Juvenile literature; Rome -- Civilization